Citation pattern and lifespan: a comparison of discipline, institution, and individual - Slyder, Jacob B.; Stein, Beth R.; Sams, Brent S.; Walker, David M.; Jacob Beale, B.; Feldhaus, Jeffrey J.; Copenheaver, Carolyn A. (Scientometrics, 2011)
Citation frequency is often used in hiring and tenure decisions as an indicator of the quality of a researcher’s publications. In this paper, we examine the influence of discipline, institution, journal impact factor, length of article, number of authors, seniority of author, and gender on citation rate of top-cited papers for academic faculty in geography and forestry departments. Self-citation practices and patterns of citation frequency across post-publication lifespan were also examined. Citation rates of the most-highly cited paper for all tenured forestry ( N = 122) and geography ( N = 91) faculty at Auburn University, Michigan State University, Northern Arizona University, Oklahoma State University, Pennsylvania State University, Texas A&M University, University of Florida, University of Massachusetts, University of Washington, and Virginia Tech were compared. Foresters received significantly more citations than geographers ( t = 2.46, P = 0.02) and more senior authors received more citations than junior researchers ( r 2 = 0.14, P = 0.03). Articles published in journals with higher impact factors also received more citations ( r 2 = 0.28, P = 0.00). The median self-citation rate was 10% and there was no temporal pattern to the frequency of citations received by an individual article ( x 2 = 176). Our results stress the importance of only comparing citation rates within a given discipline and confirm the importance of author-seniority and journal rankings as factors that influence citation rate of a given article.